A Directory of Shakespeare in Performance 1970-1990 - O'Connor, J. author. aut Link
XXVIII, 2040 p.
Keywords: This book offers detailed listings of all the major Shakespeare plays on stage and screen in North America. Exploring each of the play's performance history, including reviews and useful information about staging, it provides an engaging reference guide for academics and students alike.